DESCRIPTIVE ANALYSIS OF THE CLINICAL COURSE OF RESISTANT TUBERCULOSIS DEPENDING ON THE PATIENTS’ GENDER - Farrukh Aslonov; Isomiddin Usmonov (Central Asian Journal of Medicine, 2024)
The relevance of studying the clinical course of tuberculosis depending on the sex of patients is due to the need to develop gender-specific approaches to diagnosis, treatment, and prevention of the disease, which can improve the effectiveness of medical care. Materials and methods. This study is based on a detailed analysis of the medical records of 123 patients who underwent inpatient treatment in phthisiatric and pulmonological centers in the Bukhara and Navoiy regions of the Republic of Uzbekistan from 2019 to 2023. The prospective study included a main group of 31 patients (25.2%) treated in 2023, of which 15 patients were from the Bukhara region and 16 patients from the Navoiy region. The remaining 92 patients (74.8%) treated in the Bukhara region were included in the retrospective study and formed the comparison group. Results. Among the initial patients, out of 80 men participating in the study, 43 (53.8%) are categorized as primary patients. Out of 43 women, 31 (72.1%) are classified as primary patients. In the total sample (123 people), 74 (60.2%) are primary patients. Among the secondary patients, 37 out of 80 men (46.3%) are secondary patients, while only 12 out of 43 women (27.9%) fall into the secondary patient category. Overall, 49 out of 123 (39.8%) in the sample are secondary patients. Conclusion. Women are more likely than men to be primary patients, suggesting they seek medical help earlier or are more health-conscious, while men are more frequently secondary patients, possibly indicating higher relapse or disease progression rates in this group.